Anthropology of tourism in San Juan del Sur, Rivas Nicaragua - Espinoza Vallejos, Sandra; García Vásquez, Ramiro (Raíces: Journal of Social Sciences and Politics, 2018)
The essay presents an analysis of the tourism anthropology of San Juan del Sur from its origins to modernity, the community is located in the Department of Rivas, Nicaragua and is considered the most important tourist destination of sun and beach in the Pacific of our country. As an analytical support, the results of anthropological, archaeological, historical and updated quantitative data were reviewed in relation to the boom and development of tourism in the community. The analysis that was made through the anthropology of tourism allowed to study this economic activity, from the relationship it has with a wide diversity of human groups, between visitors and residents, which interact with each other and as a consequence a series of contacts based on in interculturality that allows a better understanding, sustainability and use of tourism, redirecting it to experiential and community typologies.